Systematic pan-cancer analysis identifies RALA as a tumor targeting immune therapeutic and prognostic marker - Jin, Haoer; Qin, Sha; He, Jiang; Xiao, Juxiong; Li, Qingling; Mao, Yitao; Zhao, Luqing (Frontiers in Immunology, 2022)
RALA is a member of the small GTPase Ras superfamily and has been shown to play a role in promoting cell proliferation and migration in most tumors, and increase the resistance of anticancer drugs such as imatinib and cisplatin. Although many literatures have studied the cancer-promoting mechanism of RALA, there is a lack of relevant pan-cancer analysis. This study systematically analyzed the differential expression and mutation of RALA in pan-cancer, including different tissues and cancer cell lines, and studied the prognosis and immune infiltration associated with RALA in various cancers. The results indicated that RALA was highly expressed in most cancers. RALA was significantly correlated with the infiltration of B cells and macrophages, as well as the expression of immune checkpoint molecules such as CD274, CTLA4, HAVCR2 and LAG3, suggesting that RALA can be used as a kind of new pan-cancer immune marker. Next, based on the genes co-expressed with RALA in pan-cancer, we selected 241 genes with high correlation for enrichment analysis. The main functions of these genes are mitosis and protein localization to nucleosome, which are related to cell cycle. In terms of pan-cancer, we also analyzed the protein-protein interaction pathway of RALA and the application of small molecule drug Guanosine-5'-Diphosphate. We screened hepatocellular cancer (HCC) to further study RALA, and the results displayed that RALA was positively correlated with common intracellular signaling pathways such as angiogenesis and apoptosis. In summary, RALA is closely related to the clinical prognosis and immune infiltration of various tumors, and RALA is expected to become a broad-spectrum molecular immune therapeutic target and prognostic marker for pan-cancer.